2018
DOI: 10.1002/pon.4945
|View full text |Cite
|
Sign up to set email alerts
|

From telling to sharing to silence: A longitudinal ethnography of professional‐patient communication about oral chemotherapy for colorectal cancer

Abstract: Background: Healthcare professionals are encouraged to promote concordance, a shared agreement about prescription and administration of medications, in their communication with patients. However, there is a paucity of research regarding the impact of communication about self-administered oral chemotherapy. The aim of this study was to examine the changing dynamics of communication through the patient journey from diagnosis of colorectal cancer to posttreatment of chemotherapy.Methods: Over 60 hours of observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Of all sixteen studies, eleven sampled patients, 4 , 11 , 13 , 20 , 24 26 , 28 , 30 32 eight sampled carers, 21 , 23 , 25 27 , 29 – 31 and five sampled HCPs. 4 , 23 , 25 , 26 , 31 All studies that sampled carers were identified as members of the patient’s family and one included an unrelated friend.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of all sixteen studies, eleven sampled patients, 4 , 11 , 13 , 20 , 24 26 , 28 , 30 32 eight sampled carers, 21 , 23 , 25 27 , 29 – 31 and five sampled HCPs. 4 , 23 , 25 , 26 , 31 All studies that sampled carers were identified as members of the patient’s family and one included an unrelated friend.…”
Section: Resultsmentioning
confidence: 99%
“…Of all sixteen studies, eleven sampled patients, 4 , 11 , 13 , 20 , 24 26 , 28 , 30 32 eight sampled carers, 21 , 23 , 25 27 , 29 – 31 and five sampled HCPs. 4 , 23 , 25 , 26 , 31 All studies that sampled carers were identified as members of the patient’s family and one included an unrelated friend. 21 Of studies involving staff, three included oncologists, 4 , 22 , 26 three nurses, 4 , 22 , 26 one recruited general practitioners, 4 one sampled surgeons, 25 and one did not specify.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Current research on chronic disease management demonstrates the importance of concordance in patient‐healthcare professional communication (Hamann et al., 2014; Kehl et al., 2015; Mitchell et al., 2019; Siouta et al., 2016). Concordance involves patients and healthcare professionals having agreed decisions about treatment based on equal relationships (Mead & Bower, 2002; Mitchell, 2014; Royal Pharmaceutical Society, 2019).…”
Section: Introductionmentioning
confidence: 99%